Study of the cytokine profile at surgeries on the lumbar spine: influence of the method of anesthesia - Lyzogub, Mykola; Leontyeva, Frieda; Skidanov, Artem; Piontkovsky, Valentyn (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Surgical interventions on the lumbar spine are performed at both general and spinal anesthesia. It is proved that any surgery is accompanied by the releasing of cytokines, but the effect of anesthesia on this process is not specified. Objective: to study the concentration of interleukin (IL)-1β, -4 and -6 in plasma patients during surgeries on lumbar spine at general intravenous or spinal anesthesia. Methods: we examined 23 patients (ASA I–II), operations on the lumar spine were performed at spinal anesthesia with 0.5 % bupivacaine (n = 11) and general propofol-fentanyl anesthesia (n = 12). We assessed IL-1β, -4 and -6 before surgery (T1), in 30 min (T2), in 3 hours (T3) and 24 hours (T4) after incision. Control group were healthy 11 people. Results: concentration of IL-1β in plasma on all stages of study was increased compare to control group (p < 0.01). Significant difference between groups and terms of study was not observed. The level of IL-6 in plasma was increased in two groups (p < 0.01). Increased concentration of IL-6 was observed in group of patients who were operate under general anesthesia during surgery (period T2) compare to preoperative period (p < 0.01) and T2 patients under spinal anesthesia (p < 0.01). During further stages significant difference was not observed. Concentration of IL-4 did not differ compare to control group none of any time period. Conclusions: degenerative disease of the spine is accompanied by increased level of inflammatory cytokines IL-1β and -6, which stay elevated at operation and during the first day after surgery. At general anesthesia in 30 min after incision we observed significant larger concentration of IL-6 compare to group of spinal anesthesia.